Generations of empire : youth from Ottoman to Italian rule in the Mediterranean - Guidi, Andreas (Toronto Italian studies., 2022)
"In 1912, Italy occupied Rhodes, an Ottoman town inhabited by Greek Orthodox, Muslims, Jews, and Catholics. Rhodes became a territory of Italy's empire in 1923 following the Treaty of Lausanne, only one year after Mussolini seized power in Rome. The Ottoman demise corresponded to the expansion of Fascist imperialism in the Mediterranean. Both the Ottoman Young Turks and Italian colonial governors invoked the role of a "new generation" of youth in imperial rule. Generations of Empire investigates the relationship between state and society in light of successive transformations of imperial rule, rethinking Italian colonialism as post-Ottoman history. Andreas Guidi explores how communal life on Rhodes and other islands of the Southern Aegean were affected by the islands' transition between these regimes, from Muslim empire to military occupation to fascist annexation. Based on archival sources in five languages from seven countries, the book investigates generational dynamics in the domains of political activism, the family, education, work and leisure, and mobility. Generations of Empire offers a vivid picture of how a local society navigated large-scale social and political transformations in the modern Mediterranean."--